Identification and functional analysis of key miRNAs and target genes associated with failure of HBV mother-to-child transmission prevention - Quan He; Xiong Zou; Chunyan Zheng; Jiawei Zhang; Jialing Li; Liping Hu; Ting Zeng; Zijuan Huang; Peipei Zeng; Jinli Wei; Haichen Cui; Yongjian Su; et al. (PLoS ONE, 2026)
Background Residual mother-to-child transmission (MTCT) of hepatitis B virus (HBV) remains a significant clinical challenge despite standard immunoprophylaxis. Identifying molecular markers is crucial for improved prevention and diagnosis. Methods We conducted a case-control study using the Guangxi Liuzhou HBV MTCT registry. Peripheral blood RNA sequencing (Illumina HiSeq) was performed on infants from HBsAg-positive mothers: cases (HBsAg-positive, n = 6) and controls (HBsAg-negative, n = 10). All infants receive HBIG and the first dose of hepatitis B vaccine within 24 hours after birth, followed by completion of the three-dose vaccination series. Differentially expressed miRNAs (DEMs; adj-p < 0.05, |log2FC| > 1) were identified. Target genes were predicted (miRanda/RNAhybrid) and functionally analyzed (GO/KEGG enrichment, PPI network). HBV-associated target genes were identified by cross-referencing GeneCards/NCBI. Results RNA-seq identified 62 DEMs (19 upregulated, 43 downregulated). Target prediction yielded 5,014 genes. Functional enrichment highlighted key pathways and processes. PPI analysis pinpointed highly connected genes. Integration with HBV databases revealed 3 key target genes potentially modulated by 4 specific DEMs (hsa-miR-6747-3p, hsa-miR-4772-3p upregulated; hsa-miR-4676-5p, hsa-miR-485-5p downregulated). Conclusion This study identifies dysregulation of 4 key miRNAs and their association with 3 HBV-linked target genes as potential contributors to residual HBV MTCT. These findings provide novel insights into the molecular mechanisms underlying HBV MTCT and suggest potential targets for intervention.